Kampung Saribu Gonjong: Pengembangan Pariwisata Budaya di Kabupaten Limapuluh Kota - Ermayanti, Ermayanti; Rahman, Fajri; Indrizal, Edi; Irwandi, Ade; Alyan, Rizka Ananda (Universitas Batanghari Jambi, 2024)
Tourism is a set of ‘machines’ that can drive the economy for regions that have tourist destinations. At present, tourism is developing according to the demands of the global market which tries to combine culture and tourism. This process is called commodification, which essentially leads to the transformation of cultural values into goods or services that have exchange value in the tourism industry. The Sarugo Village tourism area is included in the KPPK (Regency Tourism Potential Area) in Gunuang Omeh District which has cultural, religious, ecological and historical attractions. So, the development of community-based cultural tourism. This paper aims to explain the mix between culture and tourism in Sarugo Village so as to show the positive and negative effects on the culture itself or even make the culture survive. Through an ethnographic approach and data collection by observation and in-depth interviews with 15 informants, the results show that cultural aspects that are an important element in the lives of people in Sarugo Village are modified into tourism products. Rumah Gonjong is transformed into a homestay to accommodate overnight guests. This shows that the private sphere (Rumah Gonjong) turns into a public sphere in the tourism industry with the management of the local community itself. Thus, the managers of the Gonjong House, which initially only made it a place to stay, have now provided an economic increase. Therefore, the Gonjong House is currently maintained and the consequences of the tourism industry make the cultural survival of the Sarugo Village community.